Impact of concomitant obstructive sleep apnea on pulmonary involvement and main pulmonary artery diameter in adults with scleroderma - BALCAN, MEHMET BARAN; DİRESKENELİ, RAFİ HANER (SPRINGER HEIDELBERG, 2021)
Purpose Pulmonary involvement is common in adults with scleroderma. The effect of concomitant obstructive sleep apnea (OSA) on risk for pulmonary hypertension in scleroderma is unknown. An enlarged main pulmonary artery diameter (mPAD) derived from chest computer tomography (CT) is a useful predictor of pulmonary hypertension. We addressed the effect of OSA on pulmonary involvement and enlarged mPAD in adults with scleroderma. Methods All participants underwent pulmonary function testing, carbon monoxide diffusion capacity, chest CT, and overnight sleep recording with home sleep apnea testing. OSA diagnosis was based on an apnea-hypopnea index (AHI) >= 15/h. Oxygen desaturation index (ODI) was also recorded. Scleroderma involvement of the lungs was defined as the Warrick score >= 7 based on the CT findings. Enlarged mPAD was defined as an mPAD >= 29 mm in men and >= 27 mm in women. Results After exclusions, 62 patients (58 women) were included. OSA was found among 20 (32%), 17/42 (38%) in the limited cutaneous type, and 3/20 (15%) in the diffuse cutaneous type (p = 0.08). Scleroderma involvement of the lungs was observed in 40 participants (65% in OSA vs 64% in no-OSA; n.s.). Enlarged mPAD was measured in 16 participants, 10 of 20 (50%) in the OSA group and 6 of 17 (14%) in the no-OSA group (p = 0.003). OSA was associated with enlarged mPAD (odds ratio 4.7, 95% confidence interval 1.1-20.9; p = 0.042) independent of age, body mass index, and pulmonary involvement. There was a linear relationship between mPAD and AHI (r = 0.37; p = 0.003) as well as ODI (r = 0.41; p < 0.001). Conclusions In this cohort, OSA was associated with risk for pulmonary hypertension independent of pulmonary involvement. These findings suggest that assessing the effect of therapy for concomitant OSA in patients with scleroderma is warranted.
Keywords: Obstructive sleep apnea; Scleroderma; Pulmonary involvement; Pulmonary hypertension; SYSTEMIC-SCLEROSIS; COMPUTED-TOMOGRAPHY; DAYTIME SLEEPINESS; HYPERTENSION; DISORDERS; COMMON